2018
DOI: 10.1111/bjh.15705
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of prothrombin complex concentrate in patients treated with rivaroxaban or apixaban compared to warfarin presenting with major bleeding

Abstract: Summary This retrospective study investigated the efficacy and safety of prothrombin complex concentrates (PCCs) for management of major bleeding events (MBE) in 344 patients receiving the anticoagulants rivaroxaban, apixaban or warfarin during the period January 2016 to April 2018. Median (range) PCC dose was 2000 units (1000–4500). Intracranial haemorrhage (ICH) was the most common indication (137/344, 39·8%) for PCC use followed by gastrointestinal bleeding (93/344, 27%). ICH patients more frequently receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 31 publications
1
17
0
2
Order By: Relevance
“…Moreover, thrombin generation was not normalized in most cases with 4F‐PCCs until the inhibitors had been substantially cleared, 21 a finding consistent with the present study showing that 4F‐PCCs did not normalize TF‐TG unless FXa inhibitor levels were <35‐75 ng/mL (Table 2; Figure 5). Regarding bleeding patients on FXa inhibitors, several observational studies have reported on the use of 4F‐PCCs but have shown inconsistent efficacy results 24‐27 . In the light of the current study, the data in these four major reports are difficult to interpret because anti‐FXa levels were measured in only 122 of 361 (34%) patients taking apixaban and rivaroxaban spanning these four PCC studies.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Moreover, thrombin generation was not normalized in most cases with 4F‐PCCs until the inhibitors had been substantially cleared, 21 a finding consistent with the present study showing that 4F‐PCCs did not normalize TF‐TG unless FXa inhibitor levels were <35‐75 ng/mL (Table 2; Figure 5). Regarding bleeding patients on FXa inhibitors, several observational studies have reported on the use of 4F‐PCCs but have shown inconsistent efficacy results 24‐27 . In the light of the current study, the data in these four major reports are difficult to interpret because anti‐FXa levels were measured in only 122 of 361 (34%) patients taking apixaban and rivaroxaban spanning these four PCC studies.…”
Section: Discussionmentioning
confidence: 66%
“…Of note, this is the only study of the four that had consistent serial imaging of ICH, similar to the mandatory CTs required in ANNEXA‐4. The other three studies reported a benefit of PCCs in patients with major bleeding on rivaroxaban or apixaban with overall hemostatic efficacies of 69% (84 patients, Majeed et al 24 ), 65% (66 patients, Schulman et al 25 ), and 74% (80 patients, Arachchillage et al 27 ). In these three studies, one can estimate that ~25% or more of the patients were in the lower ranges of anticoagulation, similar to that seen in ANNEXA‐4 for patients with anti‐FXa levels <75 ng/mL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the full-text review, 14 case series met inclusion criteria for this systematic review without exclusions. [18][19][20][21][22][23][24][25][26][27][28][29][30][31] An additional nine case series available as abstracts only were included in the sensitivity analysis only. [32][33][34][35][36][37][38][39][40] Characteristics of case series The impact factor of journals in which case series were published ranged from 0.0420 to 16.562 (median, 2.873) (online supplemental eTable 1).…”
Section: Literature Searchmentioning
confidence: 99%
“…Thromboembolic events were statistically similar across the groups at 2.5-5.1%. There was no difference in transfusion of other products among the three groups (Arachchillage et al, 2019). Arachchillage also retrospectively evaluated patients undergoing cardiac surgery whose anticoagulation therapy was treated with PCC or FFP and found among the PCC group significantly less cardiac failure related to circulatory overload; no difference was reported in 30 days mortality, kidney injury, or thrombotic events.…”
Section: Prothrombin Complex Concentrate For Reversal Of Anticoagulatmentioning
confidence: 98%